Adapting the CROPGRO model to simulate growth and production of Brassica carinata, a bio‐fuel crop. Issue 7 (14th May 2021) - Boote, Kenneth J.; Seepaul, Ramdeo; Mulvaney, Michael J.; Hagan, Austin K.; Bashyal, Mahesh; George, Sheeja; Small, Ian; Wright, David L.
Abstract: Carinata ( Brassica carinata ) is an oilseed crop which, because of its non‐edible oil composition and favorable fatty acid profile, is proposed as a "green" sustainable aviation fuel. It can be grown as a winter crop in the southeastern USA or as a summer annual crop in northern latitudes. No crop models exist for carinata because it is a relatively new crop. The CROPGRO model is a mechanistic crop simulation of daily crop growth and development as a function of daily weather, soil properties, crop management, and species parameters. We adapted the CROPGRO model to simulate carinata based on growth analysis data collected over two seasons at three sites: Quincy, FL, Jay, FL, and Shorter, AL. The adaptation process required literature knowledge as well as optimization against field observations. The parameterization of model sensitivities to climatic factors is presented. The adapted model gave good simulations of carinata growth dynamics compared to observed growth during different seasons and locations and in response to N fertilization. While additional testing is appropriate, the model is sufficiently ready to be used for various applications. An example application is presented for the effect of sowing date on carinata yield and maturity over long‐term weather in the Southeastern USA. Abstract : Dynamic crop simulation models are useful tools for evaluating crop response to daily weather, soils, management, and genetic traits. However, no models exist for carinata, a non‐food oilseed crop with biofuel potential. We developed the CROPGRO‐Carinata model by optimization against time‐series growth and yield data collected over two seasons at three sites in the Southeastern USA. The model was parameterized for tissue composition, cardinal temperatures, productivity, phenology, and partitioning. The model satisfactorily simulates growth and yield response to cool versus warm seasons, N fertilization, and sowing date. It can be used to explore carinata cropping strategies for the Southeastern USA.